A Methods engineering study on DermPharma, Inc. - Ocampo, Elaine M. (College of Engineering, 2000)
The study was conducted at DermPharma, Inc., a company that manufactures cosmeceutical products under the trade names of Skintel, Isac 5 percent, Pregroe, Nuderm, DermPlus and Derm A System. The study aims to solve existing problems to bring about improvements for the company using the tools learned in Methods Engineering. Through observations, personnel interviews and documents disclosed by the company, the study group has analyzed and documented the existing systems and procedures, production systems framework, products, processes, layout, materials, machines, manpower and working conditions of the plant. With the given information, the study group has identified the main problems encountered in the plant and these are unnecessary movements and production delays. To address these problems, the study has come up with the recommendations, and alternatives generated were evaluated against the musts and wants objectives. Among these alternatives solutions were chosen as the following : fix existing layout, provide good housekeeping, conduct time study, establish good relationship with suppliers, production schedule based on capacity, utilization of available machine, proper material handling and storage, labeling of work-in-process, implementation of standard operating procedure and strict supervision. The alternatives were assessed against the risks and threats, the cost and time factor essential in the implementation of the aforementioned solutions. Preventive and Contingency plans and Work Standard Operating procedure were provided in the process of standardizing and maintenance of the solutions in order to achieve the desired improvements for the company.